The impact of emotional exhaustion on the performance of SMEs - Cintya Lanchimba; Dianne H. B. Welsh; Carlos Valladares (Journal of Innovation & Knowledge (JIK), 2025)
This study examines the impact of emotional exhaustion on business performance, with a particular focus on small and medium-sized enterprises (SMEs). To achieve this objective, data were collected from business owners in the developing economy of Ecuador. The research specifically explores how the effects of emotional exhaustion vary according to the gender of the business owners and investigates the role of social support in family businesses as a psychological protective factor that may help mitigate the negative consequences of emotional exhaustion. The methodology is based on quantile regression, which facilitates the analysis of the effects of emotional exhaustion across various quantiles of the conditional distribution of business performance. The results reveal that emotional exhaustion has a negative and statistically significant effect on business performance, with businesses led by men showing more pronounced effects. However, family businesses experience a mitigating effect because their organizational structure provides social support that helps counterbalance the detrimental impact of emotional exhaustion. The results underscore the need to consider both the gender of entrepreneurs and the structural characteristics of businesses when designing strategies to improve business performance and resilience. The study provides valuable insights into academic research and business practice, with practical recommendations grounded in the relevant academic literature.
Keywords: C01; M02; L01; 650; Business performance; Emotional exhaustion; Resilience; Life satisfaction; Gender